2002
DOI: 10.1007/s00417-002-0469-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 0.005% latanoprost once daily on intraocular pressure in glaucomatous patients not adequately controlled by beta-blockers twice daily: a 3-year follow-up

Abstract: Latanoprost 0.005% once daily significantly reduces IOP in the majority of glaucomatous patients uncontrolled by beta-blockers. The reduction of IOP was statistically significant during 3 years of follow-up, confirming the clinical efficacy of this compound. The ocular side effects requiring cessation of therapy were mainly allergic reactions. The most severe adverse effects were one case of corneal punctate erosion and one case of cystoid macular oedema in a pseudophakic patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 29 publications
3
20
0
3
Order By: Relevance
“…23 However, previous clinical trials with latanoprost monotherapy, another prostaglandin analogue, have established a long-lasting daytime hypotensive effect with little evidence of tachyphylaxis, for up to 4 years. [24][25][26][27][28] This is further corroborated by the present long-term 24-hour study, which documented consistent IOP efficacy with travoprost monotherapy in POAG patients during the 5-year follow-up period.…”
Section: Discussionsupporting
confidence: 78%
“…23 However, previous clinical trials with latanoprost monotherapy, another prostaglandin analogue, have established a long-lasting daytime hypotensive effect with little evidence of tachyphylaxis, for up to 4 years. [24][25][26][27][28] This is further corroborated by the present long-term 24-hour study, which documented consistent IOP efficacy with travoprost monotherapy in POAG patients during the 5-year follow-up period.…”
Section: Discussionsupporting
confidence: 78%
“…Evidences demonstrate that latanoprost may cause corneal punctate erosions 26 and inhibit corneal epithelial migration. 27 However, little has been known about how latanoprost influences the physiological functions of corneal stromal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Ten of the 15 trials involved a PGA. 44,53,56,103,114,169,[170][171][172][173] Subjects (n = 1571) switched to latanoprost from previous glaucoma monotherapy and fixed and unfixed combination therapies maintained IOP to an acceptable level through a 2-year period. 174 Latanoprost-insensitive patients developed IOP lowering with bimatoprost in a randomized prospective study with two 30-day treatment phase and 30-day washout phase.…”
Section: Rank Order Of Ocular Hypotensives As Monotherapymentioning
confidence: 99%
“…Pooling 8 studies, 113 the greatest difference in IOP lowering effect was observed with latanoprost in Mexican and Asian clinical trials. A prospective unmasked study (n = 76) 114 found latanoprost reduced IOP from 26.5 ± 6.6 mmHg to 17.4 ± 2.7 at 3 years in timolol unresponsive eyes.…”
mentioning
confidence: 99%